Ore-waste and ore type classification using portable XRF: a case study of an iron mine from the Quadrilátero Ferrífero, Brazil - Urbano, Emílio Evo Magro Corrêa; Costa, João Felipe Coimbra Leite; Graça, Leonardo Martins; Scholz, Ricardo Augusto Cipriano (Geologia USP. Série Científica, 2020)
Grade control is a fundamental activity for Short-Term Mine Planning as it validates the ore-waste and ore type classification of mine faces. Geological mapping and quasi-mining sampling provide indispensable information for the Short-Term Mine Planning team to update block models and for grade control of the run-of-mine (ROM). However, laboratory turnaround can take too long and not be timely for operational needs, affecting mining efficiency. To propose a solution for this issue we tested the accuracy of portable X-Ray Fluorescence (XRF) for ore-waste and ore type classification according to iron and phosphorus grade. Thus, iron ore run-of-mine samples from the Quadrilátero Ferrífero were analyzed with the portable XRF as pressed pellets. As a result, the overall accuracy of ore-waste classification was above 92% for different cut-off grades. On the other hand, while ore type classification had a better accuracy without calibration factors for iron, the use of calibration factors significantly improved the accuracy of ore type classification for phosphorus. Therefore, despite the portable XRF presenting good accuracy for ore-waste and ore type classification, further developments are still necessary on automatic information processing systems and sample support validation so that this analytical tool can be used on a large scale by grade control teams. Finally, the combined use of portable XRF and other techniques, such as Hyperspectral Sensing or XRD, can be of great value for mine operations.